Planning for Industrial Plantations - Kaushik, R. C.; Qureshi, I. M. (Indian Forester, 1969)
The importance of industrial plantations has received due consideration in forestry development plans of the country. In the first two plans (1951-56 and 1956-61), nearly 2,65,800 ha of plantations of valuable species were raised, followed by 84,8OO ha of plantations of quick growing species like Eucalyptus and 2,38,300 ha of economic species like teak, sissoo, rosewood, etc., in the Third Plan (1961-66). During 1966-67, 1967-68, another 2,12,000 ha of plantations of industrial woods were undertaken. During the IV Plan the target for plantations of quick-growing species is envisaged as 4,50,OOO ha at a cost of approximately 310 million rupees. Though the country has more than 1 million ha under plantations today, there are some aspects of silviculture, management and economics of industrial plantations which need immediate attention both in respect of present requirements and future planning to achieve maximum efficiency and benefits. Briefly, these are: (i) Selection of species to suit not only the site but also the end-products. (ii) Size of industrial plantations and diversification of species with due regard to pests and diseases, protection from fire, market trends and technological developments, etc. (iii) Seed supply, testing, and use of improved seeds and provenances. (iv) Plantation techniques, mechanisation, etc. (v) Initial espacement, correlation of growth with productive potential of site. (vi)Use of fertilisers and manures.(vii)Testing for Wood-Quality.(viii)Rotation and Yield.(ix)Economics of Investments and Returns.(x)Research Needs. The paper focusses attention on the above aspects in relation to present conditions and requirements for future.